The Invisible Burdens of Burden-Sharing - Thomson, Marnie Jane (Frontiers in Human Dynamics, 2022)
Within the global humanitarian realm, there is much discussion and concern for the burdens that states endure when it comes to refugee populations. The word “burden” appears in the Preamble of the 1951 Refugee Convention in reference to placing “unduly heavy burdens” on particular host countries and compels the international community to intervene in such situations. While there have been attempts to change the language from burden sharing to responsibility sharing, the emphasis on states assuming the “burden” of hosting and providing for refugee populations continues. Even as the 2018 Global Compact for Refugees has brought refugees into the discussions of international response to refugee situations, the language and concerns about burden sharing remain relatively unchanged. This is clearly demonstrated by the first ever Global Refugee Forum, which was held in December 2019, through its central theme of burden and responsibility sharing. At the forum, refugees advocated for their continued and increased inclusion, but while state delegations and humanitarian organizations acknowledged this as a benefit for all, their statements continued to assert their concerns about their positions as donor and host countries. This continued privileging of the state, even amidst the added language and practices of inclusion of all humanitarian actors, still renders invisible the burdens that refugees bear, many of which are exacerbated by the language and logics of burden sharing applied to states. A prime example of this, Trump’s anti-immigration policies and rhetoric demonstrate how state attempts to lighten their burden have far reaching effects, including long-lasting everyday burdens for those who have already been resettled. Long term ethnographic research in refugee camps and with resettled refugees provides the empirical evidence to engage in the critical policy analysis and discourse analysis of burden sharing in this piece.